INFLATION IN THE DIGITAL PAYMENT ERA: THE MODERATING EFFECT OF E-MONEY TRANSACTIONS IN INDONESIA - Kurniawan, Rudi; Purusa, Nanda Adhi; Chasanah, Amalia Nur; Riyanto, Fery (Jurnal REP (Riset Ekonomi Pembangunan), 2025)
As the use of digital payment systems through e-money increases, inflation control requires a measurable monetary policy mechanism. This study aims to examine the effect of the money supply on the inflation rate and measure the moderating role of e-money transactions. This study employs a quantitative method using time series data for the period from January 2018 to March 2025, resulting in a total of 87 months. Data analysis uses simple linear regression and the Moderated Regression Analysis (MRA) absolute difference test to test the moderating effect of e-money transactions. The results of this study indicate that there is no significant effect between the money supply and the inflation rate. However, the moderating role of e-money transactions can significantly strengthen the relationship between the money supply and the inflation rate. This finding suggests that the monetary policy mechanism should consider technological developments that can impact the payment system, thereby providing a basis for more accurate decision-making.